Utilizing the topology of configuration space in real-time multiple manipulator path planning - Maciejewski, Anthony A., author; Fox, J. J., author; ACTA Press, publisher (Colorado State University. Libraries, 2001)
This article provides a set of algorithms that allow qualitative information regarding the connectivity of configuration space to be quickly established. A mechanism is presented that utilizes these results to determine the effects of the motions of one manipulator on the configuration space of the other. These algorithms are then used as a basis for a simple planner that is capable of rapidly computing collision-free paths for multiple SCARA manipulators operating within overlapping workspaces.
Keywords: multiple manipulators; obstacle avoidance; path planning